Motivation, overtraining, and burnout: Can self-determined motivation predict overtraining and burnout in elite athletes? - Lemyre, P.-N.; Roberts, G. C.; Stray-Gundersen, J. (European Journal of Sport Science, 2007)
The aim of this study was to determine whether quality of self-determined motivation at the start of the competitive season in elite athletes and symptoms of overtraining can predict athlete burnout propensity at the end of the season. The participants were 141 elite winter sport athletes. In September, at the beginning of the season, the athletes responded to a self-determined motivation questionnaire, while they answered questions assessing overtraining symptoms and burnout in March, at the end of the season. Findings indicated that self-determined motivation and symptoms of overtraining were negatively and positively linked respectively to dimensions of athlete burnout. The results suggest that self-determined motivation and symptoms of overtraining are both independently linked to signs of burnout in elite athletes and that although no moderating effect was found, pairing self-determined motivation with symptoms of overtraining increased the prediction of burnout in athletes at the end of the season. Our findings are in line with those of recent research (Cresswell & Eklund, 2005; Lemyre, Treasure, & Roberts, 2006) and support a motivational approach to study burnout in elite athletes.